Promoting bone morphogenetic protein signaling through negative regulation of inhibitory Smads - Itoh, Fumiko (Oxford University Press, 2001)
Inhibitory Smads, i.e. Smad6 and Smad7, are potent antagonists of the BMP–Smad pathway by interacting with activated bone morphogenetic protein (BMP) type I receptors and thereby preventing the activation of receptor-regulated Smads, or by competing with activated R-Smads for heteromeric complex formation with Smad4. The molecular mechanisms that underlie the regulation of I-Smad activity have remained elusive. Here we report the identification of a cytoplasmic protein, previously termed associated molecule with the SH3 domain of STAM (AMSH), as a direct binding partner for Smad6. AMSH interacts with Smad6, but not with R- and Co-Smads, upon BMP receptor activation in cultured cells. Consistent with this finding, stimulation of cells with BMP induces a co-localization of Smad6 with AMSH in the cytoplasm. Ectopic expression of AMSH prolongs BMP-induced Smad1 phosphorylation, and potentiates BMP-induced activation of transcriptional reporter activity, growth arrest and apoptosis. The data strongly suggest that the molecular mechanism by which AMSH exerts its action is by inhibiting the binding of Smad6 to activated type I receptors or activated R-Smads.